Pengaruh Independensi Dan Kompetensi Aparat Inspektorat Kota Ambon Terhadap Kualitas Audit - Theodora F. Tomasoa (Universitas PGRI Madiun, 2020)
To realize Good Governance in the regional government area, government must make reform in all aspects of regional financial management. One of the steps by regional government is to carry out audit reforms, both internal and external in the administration of government. Through audit reforms it is expected that audit activities in the government environment can more optimally, so as to readuce the occurrence of procedural errors and criminal acts that have an impact on state losses. This research aims to test and analyze the influence of independence and competence of Ambon City Inspectorate of the Audit quality both simultaneously and partially. The population in this study is all government functional apparatus that works at the Ambon City Inspectorate Office, which serves as a sample of research using the census method where the sample equals the population. Independent variables in this study are independence and competence, while the dependencies variable is the quality of the audit. Data collection methods used in this research is a survey method using a detailed questionnaire. The questionnaire was disseminated as many as 38 questionnaires, but only 36 questionnaires were returned. The collected Data is analyzed by descriptive and statistical techniques. The results showed that by partial (1) The independence of the city's Inspectorate of Ambon has an effect on audit quality. (2) The competence of the city's inspectorate of Ambon affects audit quality. (3) simultaneously the independence and competence of the City of Inspectorate Ambon has an effect on the quality of audit.Keywords: independence, competence, and Audit quality.